Occurrence and antimicrobial susceptibility of Salmonella enterica in milk along the supply chain, humans, and the environment in Woliata Sodo, Ethiopia - Seblewengel Ayichew; Ashagrie Zewdu; Bekele Megerrsa; Teshale Sori; Fanta D Gutema (BMC Microbiology)
Abstract Background Salmonella enterica is a major cause of foodborne illness and mortality worldwide, but its presence in milk along the milk supply chain and associated public health risks are under-studied. This research was aimed to investigate the occurrence and antimicrobial susceptibility of Salmonella enterica in milk, milking environments, milkers’ hands, and diarrheic patients in Wolaita Sodo, Ethiopia. Methods We collected 644 samples from 106 dairy farms that include direct milk from cow, bulk tank milk, milkers’ hand swabs, teat surfaces swabs, farm floors swabs, milk storage containers swabs, collectors’ bulk milk, retailers’ bulk milk, and stool from diarrheic patients. Salmonella enterica was isolated using standard microbiological methods (culture-based detection, serology and PCR), and antimicrobial susceptibility was tested using the Kirby–Bauer disk diffusion method against 14 antimicrobials. Results The overall occurrence of Salmonella enterica was 1.86% (12/644). The detection rate was 2.06% (7/339: 95% CI: 1.0–4.20) along the milk supply chain, 1.94% (2/103:95% CI: 0.53–6.81) in diarrheic outpatients and 1.49% (3/202: 95% CI: 0.51–4.27) in the milking environments. Relatively, higher contamination rate (6%, 3/50; 95% CI: 2.06–16.22) was observed in milk samples collected from milk collectors. The isolates exhibit higher resistance to clindamycin (100%), erythromycin (100%), vancomycin (100%), amoxicillin (100%), ceftazidime (100%), and ampicillin (75%). Of the isolates, 92%, 83% and 67% were susceptible to norfloxacin, ciprofloxacin and Trimethoprim, respectively. All the isolates were multidrug resistant (MDR). Conclusions The study findings showed the occurrence of a considerable proportion of antimicrobial resistant Salmonella enterica across all sample sources, indicating potential transmission risks between cattle and humans via milk, and the milking environment. The alarming multidrug-resistant strains limit treatment options and complicate pathogen control. To prevent transmission and spread of antimicrobial resistant pathogen, proper hygiene practices, public education, and antimicrobial stewardship are essential. These measures will help ensure the safety of milk and dairy products. Further research on genetic relatedness among isolates, quantifying public health risks of milk consumption, and cost-effective intervention options is needed to reduce Salmonella-related morbidity and mortality.